The science of in-situ remediation - Gimpelson, Laura J. (Engineering cases, 2012)
The goal of in situ chemical oxidation (ISCO) is to destroy the chemicals of concerns (COCs) in place, with as little interference with site and adjacent property use or subsurface structures. In order to achieve this goal, it will require the engineer to look beyond the black box approach when specifying the reagent and injection process to use.